Vegetative regeneration of beech coppices for biomass in Piedmont, NW Italy. (December 2017) - Vacchiano, Giorgio; Berretti, Roberta; Brenta, Pierpaolo; Meloni, Fabio; Motta, Renzo; Nosenzo, Antonio; Terzuolo, Pier Giorgio
Abstract: Interest in coppices is growing due to the need to replace fossil fuels with renewable energy sources. In Italy, beech covers one million hectares, half of which originated by coppicing. This study tested which factors drive the presence and growth of beech resprouts, with a focus on fertility, cutting intensity, age, and size at time of coppicing. We analyzed 509 stools in 24 stands coppiced between 1 and 26 years before sampling. We fitted Generalized Linear Mixed Models of the probability of sprouting and height of the tallest resprout for each stool as a function of elevation, slope, aspect, bedrock, precipitation, temperature, age at coppicing, time since coppicing, residual shoot density, the sum, average and coefficient of variation of the diameter of cut shoots, and type of stool treatment. Of all harvested stools, 249 (49%) had sprouted with an average of 7.6 resprouts per stool. Height of the tallest resprout on each stool ranged from 3 to 800 cm, mainly as a function of time since coppicing. Resprout mortality was on average 1.4% per plot. Sprouting decreased with decreasing site fertility, increasing precipitation, and increasing size of cut stems. Leaving one or more shoots on the stool after felling produced a high proportion of sprouting stools (82%). Although based on a limited sample, our quantitative analysis of the driving factors of sprouting in beech can be used to support silvicultural decisions in over-mature beech coppices, and to optimize trade-offs between ecosystem services such as biomass production, biodiversity, and hydro-geologic protection. Highlights: Forest coppicing allow to replace fossil fuels with renewable energy sources. We tested which factors drive the probability and vigor of beech sprouting in the Italian Alps. Sprouting decreased with poor soils, higher precipitation and increasing stool size. When one or more shoots were left, 82% of the stools sprouted. This evidence can be used to sustainably manage beech coppices for biomass.